Stable perovskite based photodetector in impedance and capacitance mode - Qasuria T.A.; Alam S.; Karimov K.S.; Fatima N.; Alharthi Y.S.; Alharbi H.F.; Alharthi N.H.; Amin N.; Akhtaruzzaman M. (Elsevier B.V., 2023)
Nowadays perovskite emerges as a promising photosensitive material for next-generation solution-processed devices. Perovskite-based solar cells degrade in ambient conditions up to some extent, after which they are discarded. In our work, we are using reusing the degraded cells as a high-performance stable perovskite-based photodetector. The symmetry of the detector is FTO/PEDOT:PSS/Perovskite/PC61BM/CdS/Ag showing sensitivity to light with respect to (w.r.t) impedance and capacitance. To enhance the excitons generation and absorption of light, the electron transport layer of cadmium sulfide along with PC61BM is selected and PEDOT:PSS layer is used for hole transportation. Atomic force microscopy, X-ray diffraction, and UV-absorption spectrum were obtained to study the surface morphology, composition, and absorption of the perovskite layer. The electric parameters within the frequency range 100 Hz to 200 kHz of samples under the effect of light were investigated. Experimental results showed that with the change in light intensity from dark to 325 W/m2, the highest impedance and capacitance were observed at 100 Hz. The impedance sensitivity is ?126.154 k? m2/W and the uppermost capacitance sensitivity w.r.t light intensity is 6.77 pF m2/W. Frequency-impedance and capacitance relationships and sensitivities were also measured. The results showed that in the range from 100 Hz to 200 kHz the maximum impedance sensitivity is ?343.37 ?/Hz in dark condition. While the capacitance sensitivity was highest when light intensity was 325 W/m2 (?37.27 pF/kHz), respectively. We attribute these observations due to the generation of electron-hole pairs under light and by the increase of their concentration, by the presence of the built-in capacitance and possible frequency dependence of the mobility of the charges. 2019 The Authors